Single longitudinal mode narrow linewidth thulium-doped fiber laser based on an eye-shaped dual-ring filter - Wang, Xiangdong; Yan, Fengping; Guo, Hao; Wang, Wei; Qin, Qi; Yang, Dandan; Wang, Pengfei; Li, Ting; Yu, Chenhao; Guan, Biao; Kumamoto, Kazuo; Suo, Yuping; et al. (Frontiers in Physics, 2023)
A single-longitudinal-mode (SLM) thulium-doped fiber laser, based on an eye-shaped passive dual-ring filter, is designed and constructed. The eye-shaped passive compound cavity consisting of four couplers is used to increase the longitudinal mode spacing, and its performance is numerically analyzed in detail. A homemade uniform fiber Bragg grating serves as a wavelength selection device, and a saturable absorber is used to further suppress the intense longitudinal mode competition in the laser cavity, ensuring the SLM output. The experimental results demonstrate a laser output with a center wavelength of 2049.85 nm and an optical signal-to-noise ratio of 63 dB. Moreover, the power fluctuation is less than 0.6 dB, and the center wavelength fluctuation is less than 0.03 nm over a continuous measurement period of 60 minutes, demonstrating an excellent stability. The laser linewidth is measured using an unbalanced Michelson interferometer and β-separation line method, resulting in a linewidth of 11.22 kHz.